ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN KEJADIAN HIPERTENSI PADA MASYARAKAT PESISIR - Sri Anjayati; Juminten Saimin; Fikki Prasetya (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Hypertension or high blood pressure is a significant cause of avoidable cardiovascular disease and premature death in developing countries with inadequate health care systems. The purpose of this study was to analyze factors related to the behavior of preventing hypertension in coastal communities in the working area of ​​the Kulisusu Public Health Center, North Buton Regency. The type of research was observational analytic using a cross-sectional design involving 102 people living on the coast of North Buton Regency who were selected randomly. The statistical tests used are chi square and logistic regression. The results showed that the most dominant behavior for preventing hypertension was the good category, 55 respondents (53.9%), and the least was the less category, 47 respondents (46.1%). There is a relationship between hypertension prevention behavior in coastal communities with education level (p-value = 0.002), knowledge (p-value = 0.000), information exposure (p-value = 0.000) and social support (p-value = 0.002). Information exposure is the variable that is most related to the behavior of preventing hypertension (R Square value of 35.8%). Exposure to information is the variable most related to the behavior of preventing hypertension.